4(2x-5)-3(3x+1)=6(x-2)+5x

Simple and best practice solution for 4(2x-5)-3(3x+1)=6(x-2)+5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x-5)-3(3x+1)=6(x-2)+5x equation:



4(2x-5)-3(3x+1)=6(x-2)+5x
We move all terms to the left:
4(2x-5)-3(3x+1)-(6(x-2)+5x)=0
We multiply parentheses
8x-9x-(6(x-2)+5x)-20-3=0
We calculate terms in parentheses: -(6(x-2)+5x), so:
6(x-2)+5x
We add all the numbers together, and all the variables
5x+6(x-2)
We multiply parentheses
5x+6x-12
We add all the numbers together, and all the variables
11x-12
Back to the equation:
-(11x-12)
We add all the numbers together, and all the variables
-1x-(11x-12)-23=0
We get rid of parentheses
-1x-11x+12-23=0
We add all the numbers together, and all the variables
-12x-11=0
We move all terms containing x to the left, all other terms to the right
-12x=11
x=11/-12
x=-11/12

See similar equations:

| 14+x=169 | | 7c-6c=5-2 | | x-0.22x=63,120 | | D=55x5 | | 3x^+2x-5=0 | | 1.56^x-1=14.5 | | 2(x+4)+2x+3=3x+16 | | 8x-5+x=13 | | 2^x=4^2x+1 | | 9x=-22 | | 12=g+9 | | -1/2r-2=-27 | | p-30=81 | | 4(7x-1)-4(x+5)=12 | | P+q=100 | | 7x/10+3/2=3x/5+2 | | 6(2x-1)-5x=2(5x-4)-7 | | 0=-16t^2+60t+120 | | −1/2(4x+2)=19 | | −12(4x+2)=19 | | 128=0.125³-x | | -x/8=52 | | x+3.9=8.9 | | 25-(3x+5)=2(x+8)x | | 8+6-y=10 | | -5(x+1)=-5 | | x+5=-12+7 | | 3x=9=-6 | | (2–7i)(9+5i)=0 | | 10.3=n+4.1 | | -3/11=k/6 | | 15=2-4z |

Equations solver categories